Pendidikan Pemustaka Melalui Kegiatan Literasi Informasi di Perpustakaan STIE Perbanas Surabaya untuk Mendukung Perguruan Tinggi yang Berkualitas - Dyana Purwandini (IAIN Ponorogo, 2016)
Lifelong learning society emphasize the importance of information in a process of learning, self-development, career, doing work / business, and live in every opportunity. Lifelong learning society gives opportunities to the community, especially here is the student to respond to the demands of learning-oriented in their spare time (non formal education). The role of the library to realize a lifelong leraning society is to conduct information literacy activities with the main goal is to provide supplies to users, especially students to make it easier to complete the task of learning. Information literacy needs to be given to users, especially students is to better identify what information users need and how to do searching to the sources of information, especially that contained in the library. Library Perbanas Surabaya designing activities that support the implementation of information literacy in order to develop a lifelong learning society. The activity is Metodologi Penelusuran Informasi Ilmiah workshop and Research Zone services.